TIM-1 defines a human regulatory B cell population that is altered in frequency and function in systemic sclerosis patients. Issue 1 (December 2017) - Aravena, Octavio; Ferrier, Ashley; Menon, Madhvi; Mauri, Claudia; Aguillón, Juan; Soto, Lilian; Catalán, Diego
Abstract Background Systemic sclerosis (SSc) is a systemic autoimmune disease characterized by excessive production of extracellular matrix by fibroblasts on skin and internal organs. Although Th2 cells have been involved in fibroblast stimulation, hyperactivated B cells may also play an important role. Regulatory B cells (Bregs) are cells capable of inhibiting inflammatory responses and controlling autoimmune diseases. Although many Breg populations have in common the ability to produce high amounts of IL-10, a unique surface marker defining most human Bregs is lacking. It has been described in mice that T cell Ig and mucin domain protein 1 (TIM-1) is an inclusive marker for Bregs, and that TIM-1+ B cells are able to prevent the development of autoimmunity. The aim of this work was to evaluate TIM-1 as a marker for human IL-10+ Bregs, and to determine whether TIM-1+ B cells are defective in SSc patients. Methods SSc patients (n = 39) and 53 healthy subjects were recruited. TIM-1 and IL-10 expression was assessed in resting or activated peripheral blood CD19+ B cells by flow cytometry. The regulatory function of TIM-1+ or activated B cells from SSc patients and healthy subjects was assessed in autologous and allogenic co-cultures with CD4+ T cells, where T cell proliferation and IFN-γ, IL-17, TNF-α and IL-4 production by T cells was measured by flow cytometry. Results TIM-1 and IL-10 were preferentially expressed in transitional B cells, but were upregulated in naïve and memory B cells upon stimulation. The frequency of transitional TIM-1+ IL-10+ B cells was significantly decreased in SSc patients compared to healthy controls. In addition, activated B cells from SSc patients induced stronger allogenic Th1 and Th2 responses than activated B cells from healthy controls. Finally, TIM-1+ B cells, including transitional and non-transitional cells, exhibited a higher CD4+ T cell suppressive ability than TIM-1− B cells in healthy controls, but not in SSc patients. Conclusions TIM-1 is a unique marker for the identification of a human IL-10+ Breg subpopulation which is partially superimposed with transitional B cells. Alterations in TIM-1+ B cells could contribute to the development of autoimmune diseases such as SSc.